Clinical Learning Environment: Perceptions of Palestinian Nursing Students - Bahaaeddin M. Hammad PhD; Faeda A. Eqtait PhD; Basma Salameh PhD; Ahmad Ayed PhD; Imad H. Fashafsheh PhD (SAGE Publishing, 2024)
Clinical learning environment play a vital role in bridging theory with practice, equipping nursing students with essential skills for patient care and support their smooth transition into the nursing workforce. To assess Palestinian nursing students' perceptions of clinical learning environment and supervision. A total of 308 undergraduate nursing students were conveniently recruited from Arab American University-Palestine for this descriptive cross-sectional study. Data collection utilized the Arabic version of the Clinical Learning Environment and Supervision plus Nurse Teacher scale. In general, nursing students expressed positive perceptions regarding their clinical learning environment ( M  = 130.56 ± 21.03), with the "supervisory relationship" and "role of nurse teacher" scoring highest ( M  = 3.85 ± 0.82 each). Conversely, the lowest rating was observed for "leadership style of the ward manager" ( M  = 3.8 ± 0.84). Fourth-year students and those trained in public hospitals showed significantly more positive perceptions ( P  < .001). Furthermore, students with higher professional satisfaction had more positive perceptions of the clinical learning environment ( P  < .001). The positive perceptions of Palestinian nursing students underscore the importance of the supervisory relationship and nurse teacher. However, finding suggest an area for improvement in the leadership style of the ward manager, emphasizing the necessity for strengthened partnership between nursing faculties and healthcare facilities. These insights expand our understanding of student perceptions and stress the importance of addressing these concerns to adequately prepare students for professional practice.